LINGUISTIC FEATURES OF ENGLISH ADVERTISING SLOGANS IN EDUCATIONAL SERVICES - Abdurakhmanova Sarvinoz Orifjon qyzy (International Journal of Literature and Language Studies, 2026)
This article examines the linguistic characteristics of English-language advertising slogans in the educational sector. Based on a corpus of 50 slogans from leading international universities and educational platforms (2023–2025), the study identifies lexical, stylistic, and syntactic patterns that distinguish educational advertising from commercial consumer advertising. The findings reveal a predominance of lexical fields related to